Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Karyawan pada Saka Hotel Medan - Lukas Todo Panggabean; Husni Mubarak (CIVITAS: Jurnal Studi Manajemen, 2022)
Employee performance is one of the important points that every company needs to pay attention on and for its sustainability. Several factors that influence employee performance and also examined in this study are training and motivation. This research was conducted in order to overcome the problems about the provision of training, motivation and employee performance at Saka Hotel Medan. This study used a questionnaire as a test instrument and was distributed to 49 employees of Saka Hotel Medan. The result of this research was to find out whether there was an influence between training and work motivation towards employees performance on Saka Hotel Medan. The method of this research was a quantitative method with multiple linear regression analysis technique. The data used comes from a questionnaire that is distributed internally and hypothesis testing using the coefficient of determination (R2), Simultaneous Test (F), and Partial Test (t). The results of this research indicate that simultaneously and partially showed that training and work motivation have a significant effect on employee performance at Saka Hotel Medan. The results of this study also explain that the effect of training and motivation on employee performance is only 26%, while the rest of the percentage, employee's performance is influenced by other factors.